The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1037/0278-7393.30.4.838
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Memory for Contextual Detail.

Abstract: Generation enhances item memory but may not enhance other aspects of memory. In 12 experiments, the author investigated the effect of generation on context memory, motivated in part by the hypothesis that generation produces a trade-off in encoding item and contextual information. Participants generated some study words (e.g., hot-c__) and read others (e.g., hot-cold). Generation consistently enhanced item memory but did not enhance context memory. More specifically, generation disrupted context memory for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
166
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(191 citation statements)
references
References 48 publications
(164 reference statements)
20
166
5
Order By: Relevance
“…Although the present study investigated the effects of generation at both study and test, the generation and revelation effects have typically been studied as separate phenomena (but see Mulligan & Lozito, 2006, for a comparison of the two effects). A significant recognition advantage for words generated at study was observed in all five experiments reported here, confirming the robust nature of the generation effect in both within-groups and betweengroups designs (Begg, Snider, Foley, & Goddard, 1989;see Bertsch, Pesta, Wiscott, &McDaniel, 2007, andMulligan, 2004, for reviews). The generation effect was also reliably present up to 4 weeks after study.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Although the present study investigated the effects of generation at both study and test, the generation and revelation effects have typically been studied as separate phenomena (but see Mulligan & Lozito, 2006, for a comparison of the two effects). A significant recognition advantage for words generated at study was observed in all five experiments reported here, confirming the robust nature of the generation effect in both within-groups and betweengroups designs (Begg, Snider, Foley, & Goddard, 1989;see Bertsch, Pesta, Wiscott, &McDaniel, 2007, andMulligan, 2004, for reviews). The generation effect was also reliably present up to 4 weeks after study.…”
Section: Resultssupporting
confidence: 64%
“…The generation effect was also reliably present up to 4 weeks after study. These findings are readily accommodated by the multifactor account of the generation effect (see, e.g., Hirshman & Bjork, 1988;Hunt & McDaniel, 1993;McDaniel, Wadill, & Einstein, 1988;Mulligan, 2001Mulligan, , 2004, according to which generation enhances item-specific processing of the target item, thereby increasing its distinctiveness. The multifactor account can explain generation effects in both within-and between-groups manipulations, as were found in the present study (see Mulligan & Lozito, 2004, for a review of the multifactor account of generation effects).…”
Section: Resultsmentioning
confidence: 95%
“…For instance, in comparison with the reading condition, the letter transposition condition might produce superior encoding (and later recollection) of the cognitive operations used to encode the word (e.g., Johnson, Hashtroudi, & Lindsay, 1993). Alternatively, other aspects of the study context might be better encoded in the letter transposition condition (although see Mulligan, 2004). In either case, the greater recollection (and susceptibility to DA effects) need not be mediated by semantic information, although this idea certainly requires additional inquiry.…”
Section: Discussionmentioning
confidence: 99%
“…We note that Mulligan (2004) has recently shown that generating a studied item sometimes impairs memory for contextual features of the item. So far, this work has focused on memory for incidental aspects of context (color, location) for studied words.…”
Section: Notesmentioning
confidence: 99%